Localising the SDGs in India: The role of government and private training institutes - Sreerupa Sengupta; Avik Sinha (Deutsches Institut für Entwicklungspolitik (DIE), 2022)
The Sustainable Development Goals (SDGs) present a new and coherent way of thinking about diverse facets of development. Implicit in the framework of the SDGs is that the goals are interconnected and interdependent. To translate such critical ideas into reality, countries need new skills, perspectives and approaches to the implementation of policies and programmes. Capacity-building, in particular for the public sector, is therefore at the core of achieving the 2030 Agenda. Although all countries have designed their respective capacity-building strategies and undertaken various interventions for knowledge dissemination among government officials and other stakeholders on the SDGs, there are wide variations between countries regarding the progress on capacity-building initiatives. In many developing countries, the heterogeneity of the political, societal and economic structures poses one of the biggest challenges to capacity-building for the localisation of the SDGs. [...]
Keywords: 330